Epistemologi Pemikiran Syed Muhammad Naquib Al-Attas tentang Pengembangan Pendidikan Islam - Firda Maghfirotus S; Muklasin; Ahmad Salim Ulul Albab; Asnawan; Nur Rofi’ah (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
The abstract discusses the thought of Syed Muhammad Naquib al-Attas on the development of Islamic education through the three main aspects of the philosophy of knowledge: ontology, epistemology, and axiology. The ontological dimension presents Islamic education as the very nature of the life of rational human beings, directed toward the development of human potential on the basis of the relationship with Allah, and conceptualized through ta’lim, tarbiyah, and especially ta’dib as the most appropriate term for Islamic education. Epistemologically, al-Attas proposes a tawhidic epistemology that integrates sensory, intellectual, spiritual, and intuitive elements in an integral way, with the Qur’an, the Sunnah, and the classical Islamic scholarly tradition as its primary sources, thereby rejecting the secular epistemic paradigm of Western philosophy of science. From this synthesis emerge several principles of tawhidic epistemology that emphasize the unity of the religious and the scientific, the strengthening of the spiritual dimension, and the elimination of the dichotomy of knowledge, so that knowledge becomes a means for the formation of adab. Axiologically, Islamic education is oriented toward realizing the purpose of human life as ‘abid and khalifah, so that knowledge is not merely a technical instrument, but bears the value of worship and is directed toward the cultivation of adab, ethics, and true happiness in accordance with the Islamic worldview.